PROSESI TARI AYUN LUCI SIULAK MUKAI KERINCI SEBAGAI IDE DALAM KARYA BATIK LUKIS - Gelanti Noverza, Drs. Erwin, M.Sn. (Universitas Negeri Padang, 2019)
AyunLuci dance is a sacred traditional dance that has been inherited from generation to generation in SiulakMukaiKerinci region. Today, this dance has begun to be forgotten by society. The young generation is no longer familiar with AyunLuci dance. This condition motivates the writer to make it as the source of ideas in creating works of art. Through five stages of realization, namely; preparation, elaboration, realization of concept and completion stage, the writer succeeded in realizing 10 works entitled; 1) Luci, 2) Merias Diri, 3) Ngasap Kemenyan, 4) Mengayun Luci, 5) Ngelai, 6) Nyabung Kain, 7) Nyambai Lamat Padi, 8) Mangkuk di Ateh Kepalo, 9) Meniti Pedang Tigo Berlarik, and 10) Luci di Umo. It is recommended for students to explore traditional culture in realizing works of art.Keywords: Procession, AyunLuci Dance, Batik Painting.